The Relationship between Religion and Ethics; the Four Levels - Maryam Larijani (اخلاق وحیانی)
The close relationship between the two issues of “religion” and “ethics”, which share a lot of common propositions, is among the issues that have been given serious attention by intellectuals and scholars. In this article, to prevent from confusing the issues, first what is really meant by the terms “religion” and “ethics” has been clarified and, then, the relationship between “religion” and “ethics” has been demonstrated in four levels which are as follows: Level 1: Content relationship Level 2: The relationship due to one of these issue’s validity, authority and basis being dependent on the other in this regard; Level 3: The mutual assistance of religion and ethics to each other’s implementation and external realization regardless of the previous two levels; Level 4: The assistance they give each other in the identification of each other’s scope and content The separation of these levels will help a great deal to reach a better understanding of the relationship between “religion” and “ethics”, an issue which is addressed in this paper.